FREQUENCY OF RIGHT VENTRICULAR INFARCTION AND IN-HOSPITAL OUTCOME AFTER PRIMARY PERCUTANEOUS CORONARY INTERVENTION (PPCI) IN ACUTE INFERIOR MYOCARDIAL INFARCTION (MI) - Mohsin Saif (Army Medical College Rawalpindi, 2020)
Objective: To determine the frequency of Right Ventricle infarction and in-hospital outcome after primary percutaneous coronary intervention in patients with acute inferior MI.